2021
DOI: 10.32607/actanaturae.11062
|View full text |Cite
|
Sign up to set email alerts
|

Snail-Family Proteins: Role in Carcinogenesis and Prospects for Antitumor Therapy

Abstract: The review analyzes Snail family proteins, which are transcription factors involved in the regulation of the epithelial-mesenchymal transition (EMT) of tumor cells. We describe the structure of these proteins, their post-translational modification, and the mechanisms of Snail-dependent regulation of genes. The role of Snail proteins in carcinogenesis, invasion, and metastasis is analyzed. Furthermore, we focus on EMT signaling mechanisms involving Snail proteins. Next, we dissect Snail signaling in hypoxia, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 130 publications
0
7
0
2
Order By: Relevance
“…In fact, Snail itself has been described as sometimes having a cytoplasmatic rather than nuclear localization [ 65 ], and this could be attributed to the different posttranslational modifications of Snail that can either induce its import into the nucleus or export into the cytoplasm [ 66 ]. Although cytoplasmatic Snail does not induce EMT [ 65 ], it may have other functions as it has been shown that Snail can directly act on other proteins, such as p53, by blocking their DNA-binding domain and inhibiting their function [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Snail itself has been described as sometimes having a cytoplasmatic rather than nuclear localization [ 65 ], and this could be attributed to the different posttranslational modifications of Snail that can either induce its import into the nucleus or export into the cytoplasm [ 66 ]. Although cytoplasmatic Snail does not induce EMT [ 65 ], it may have other functions as it has been shown that Snail can directly act on other proteins, such as p53, by blocking their DNA-binding domain and inhibiting their function [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since several studies have described the roles of TGFβ1-activated SMADs in EMT induction (28), our further analyses were focused on TGFβ1/SMAD signalling target genes including the transcription factors SNAIL and SLUG which in turn induced the expression of mesenchymal genes (such as Vimentin and α-SMA) (29,30) and the repression of epithelial marker genes (such as E-cadherin and CK8/18). Western Blot analyses showed that CRC_sEVs elicited in hepatocytes the effects due to the activation of TGF-β1/SMAD signalling pathway with different time courses for the different analysed target genes.…”
Section: Crc_sevs Carrying Tgfβ1 Modulate the Expression Of Emt Marke...mentioning
confidence: 99%
“…All snail protein members encode transcriptional repressors with a similar structural organisation. The C-terminal domain is exceptionally conserved, containing four- to five-type zinc fingers (C2H2) which oversee sequence-specific binding to the E-box element (5′-CAG GTG-3′) of the target genes ( 43 ). The N-terminal in humans contains the evolutionarily conserved SNAG domain, which is important for the binding of various transcriptional corepressor complexes to enforce repression of the target genes ( 44 ).…”
Section: Emt and Metastasismentioning
confidence: 99%